'We are a community [but] that takes a certain amount of energy': Exploring shared visions, social action, and resilience in place-based community-led energy initiatives. Issue 53 (November 2015) - Parkhill, K.A.; Shirani, F.; Butler, C.; Henwood, K.L.; Groves, C.; Pidgeon, N.F.
Highlights: We engage with conceptual characteristics of 3 community-led energy case studies. We examine data from interviews to explore the issues community energy groups face. Shared visions, social action and social resilience are important to community energy. Creating and maintaining shared visions, social action and social resilience is extremely challenging. Abstract: In UK energy policy, community-led energy initiatives are increasingly being imbued with transformative power to facilitate low carbon transitions. The ways that such expectations for communities are manifesting in practice remains, however, relatively poorly understood. In particular, key conceptual developments in unpacking what constitutes 'community' that highlight the significance of 'place' along with important characteristics, such as shared visions, collective social action, and resilience, have yet to be comprehensively explored in the context of community-led energy initiatives. This paper uses an interpretive stance to engage with these conceptual ideas about community and provides insights into the nature of community and its meaning for developing energy-related initiatives and realising the wider goals of energy policy. The paper draws on data from in-depth qualitative, longitudinal interviews undertaken in two residential communities and one purely workplace-based community, which are engaged in community energy initiatives. We argue that there are difficulties and ambiguities in creating shared visions, achieving social action, and developing resilience that are related to the specificities of community in place, but that all three characteristics are likely to be important for the making of sustainable places.